Kewajiban Nafkah Hadanah Dan Rada'ah Terhadap Anak Di Indonesia - Jauhari, Iman (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Effect of  busy  parents often  neglected  duty  towards their  children.  So  in  this  paper  a  problem  concerning maintenance obligations hadanah  and rada'ah for children. The method  used  is  the  approach  to  library  research  with  content analysis  of  the various  references  relevant to  the subject matter covered.  Parents are  obliged to provide  a living  hadanah  against children because a child needs someone who can nurture, guide and  educate  well.  Obligations of  parents  towards  children  has been started  from the time  the fetus  until the baby  where  the mother  is obliged to  provide  a living  rada'ah  (feeding  the baby) in addition  to  the health  of the baby  also  for the health of  the mother.  In  Islam  keeping  the  kemaslahatan  and  survival  of  a child  is a  parental responsibility,  which should not be  ignored either by the mother or father.